Synthesis and characterization of 3D gelatin/calcium hydroxide/dentin matrix proteins/propolis scaffolds for hard tissue engineering - Sadrabad, Maryam Jalili; Torkashvand, Mohammad; Saberian, Elham; Bahraminasab, Marjan (BMC oral health, 2025)
This paper explores the development of three-dimensional porous scaffolds composed of gelatin, calcium hydroxide, dentin matrix proteins, and propolis (signified as G, Ca, DP, and P, respectively). First, the scaffolds were synthesized using freeze-drying technique, then their physicochemical properties, mechanical characteristics, cytocompatibility with dental pulp stem cells, and cell adhesion, differentiation and mineralization were evaluated. The results showed that the scaffolds were porous with asperity. The surface roughness analysis identified higher roughness value for the G-Ca-P and G-Ca-DP-P scaffolds (mean Rq of 38.16 and 21.69 nm, respectively). All the scaffolds exhibited hydrophilic behavior (contact angles < 90°). However, those having propolis, calcium hydroxide and protein showed higher wettability. Furthermore, all scaffolds degraded over time with a synergistic effect between calcium hydroxide and dentin matrix proteins in making a more robust scaffold and enhancing the alkalinizing effect. The G and G-P scaffolds had elastic-plastic behavior, while G-Ca-P and G-Ca-DP-P scaffolds showed brittleness. Moreover, all scaffolds revealed no cytotoxicity (cell viability >80%). The alkaline phosphatase (ALP) concentration and matrix deposition, as measures of osteogenic differentiation, were highest for G-Ca-DP-P scaffolds, followed by G-Ca-P. Besides, the cells attached to the scaffold surfaces with a flattened morphology, and the highest cell number adhered on G-Ca-DP-P and G-Ca-P scaffolds, respectively. Altogether, the G-Ca-DP-P scaffolds acted as hydrophilic, rough, and biodegradable frameworks supporting cell viability, adhesion, differentiation and mineralization.